Suddenly there was a tapping: Edgar Allan Poe in the dawning of speculative fiction - Martins, Cláudia (2020)
Forty years of life were what this hallmark of American literature needed to break a number of boundaries in traditional fiction in the first half of the 19th century. Edgar Allan Poe is reputed to be the architect of the modern short story (cf. Dawson, 1909) and a forerunner of the “art for art’s sake” movement in America. According to the Poetry Foundation, Poe formulated strictly artistic ideals based on the calculated use of language through which he expressed a vision of truth and the essential condition of human condition. He rejected the effect of accident or inspiration in the making of both his fiction and poetry, but rather insisted that the tiniest detail should be the result of rational deliberation. As such, Poe wrote over 40 short stories encompassing several fictional types that contemporary critics refer to as speculative fiction. Different classifications have been proposed (e.g. Howarth, 1971; Quinn, 1997), but it is commonly accepted that Poe’s tales are divided into four different styles, ranging from horror to Gothic and science fiction to ratiocination. This paper claims that Poe “tapped on the window of fiction” and brought about major changes in the literary scene of the 19th century which would bear fruit in the 20th century. By analysing a number of his renowned tales, we intend to demonstrate the full extent of his refolution in the realm of short stories.